The role of destination management in mediating the determinants of CyberjayaTourism image branding - Mehtab Alam; Mudiarasan Kuppusamy; Puvaneswaran Kunasekaran (Cogent Business & Management, 2023)
The purpose of this research is to provide Butler's tourism lifecycle model and destination management role for tourism image branding which is a missing feature in recent destination management research. It is to provide determinants of tourism destination management for branding Cyberjaya city of Malaysia as a tourist site. A quantitative research methodology using SPSS 19 and PLS-SEM 4 is employed to examine and investigate the opportunities supporting the destination's image. Results show a significant contribution of destination management determinants for image branding, where Cyberjaya city has the potential to become a destination city. The determinant of branding from exploration to rejuvenation of destination requires the personal satisfaction of tourists through the quality of accommodation, perception of beauty and managing destination infrastructure. The valuable research is to guide tourism managers to use Cyberjaya as a tourism destination city. This is to offer the travelers to visit and consider the city of Cyberjaya as their choice of stay. The Butler tourism lifecycle model is extended with this research on tourism destinations use for image branding.
Keywords: 650; image branding; management; tourism destination